-4(5t-3)+5t=4t-9

Simple and best practice solution for -4(5t-3)+5t=4t-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5t-3)+5t=4t-9 equation:


Simplifying
-4(5t + -3) + 5t = 4t + -9

Reorder the terms:
-4(-3 + 5t) + 5t = 4t + -9
(-3 * -4 + 5t * -4) + 5t = 4t + -9
(12 + -20t) + 5t = 4t + -9

Combine like terms: -20t + 5t = -15t
12 + -15t = 4t + -9

Reorder the terms:
12 + -15t = -9 + 4t

Solving
12 + -15t = -9 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
12 + -15t + -4t = -9 + 4t + -4t

Combine like terms: -15t + -4t = -19t
12 + -19t = -9 + 4t + -4t

Combine like terms: 4t + -4t = 0
12 + -19t = -9 + 0
12 + -19t = -9

Add '-12' to each side of the equation.
12 + -12 + -19t = -9 + -12

Combine like terms: 12 + -12 = 0
0 + -19t = -9 + -12
-19t = -9 + -12

Combine like terms: -9 + -12 = -21
-19t = -21

Divide each side by '-19'.
t = 1.105263158

Simplifying
t = 1.105263158

See similar equations:

| [40+10r]=27-3r | | 32-x/5=x/3 | | 3/8x+7/8=-1 | | 2x-8+5=0 | | z/3=21 | | 2s+7=3-s | | 1/5(20x+30)=1/3(6x+36) | | 5[2r+8]=27-3r | | 4(4a-2b+5)+2(2a-5)=e | | 5x+2+154=45x-4 | | 32/4*3+14*10 | | 39-3s=23(2s-3) | | 6a^2-11a-2= | | 1/2x-2/5=0 | | 4p-61=-17 | | 1/5(4-3x) | | 6g+5-3g=12-7g+9 | | x/3-15 | | -5(6y-4)-y=-2(y-4) | | 27a^2x^2+45a^2x+36a^2=0 | | -9=r+(-15) | | 10x-4+30=14x+2 | | 9x^2-86x+45= | | 1/4-(-1/2)= | | 40ax^2+24ax+32a=0 | | 4a+4-xa=a+5 | | 1/2x+7=5/2 | | 1.8y+3.5=2.5y+2.1 | | -27+20w=-73 | | 4x+4-ax=x+5 | | 40ax^2+24ax+32=0 | | w-134=211 |

Equations solver categories